2010
DOI: 10.1007/s11144-010-0199-6
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium (III)-catalyzed oxidative cleavage of phenylpropanolamine with N-bromosuccinimide in hydrochloric acid medium: a kinetic and mechanistic approach

Abstract: The kinetics of ruthenium (III)-catalyzed oxidative cleavage of phenylpropanolamine (2-amino-1-phenyl-propan-1-ol) (PPA) with N-bromosuccinimide (NBS) in HCl medium has been investigated at 308 K. The oxidation reaction follows the rate law, d, where a and b are less than unity. The stoichiometry of the reaction has been found to be 1:1, and benzaldehyde and acetaldehyde were identified as the oxidation products of PPA. The activation parameters have been evaluated from the Arrhenius plot. NBS itself has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similar studies were undertaken for the oxidation of allyl alcohol, benzyl ethers, benzhydrols, amines and amino alcohols, glycols, , cardiotoxin II,nitrones and N ,α-diphenylnitrones, , dibenzyl sulfoxide, and substituted aromatic acetals . Oxidative cleavage of thiamine hydrochlorideand phenylpropanolamine and oxidative conversion of glutathione to glutathione disulfide, were also studied in a similar context. During the study of the oxidation of azides with NBS, it was observed that the rate of oxidation of N 3 – in an aqueous medium is proportional to [N 3 – ] and [NBS] at constant [Hg(OAc) 2 ] .…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Similar studies were undertaken for the oxidation of allyl alcohol, benzyl ethers, benzhydrols, amines and amino alcohols, glycols, , cardiotoxin II,nitrones and N ,α-diphenylnitrones, , dibenzyl sulfoxide, and substituted aromatic acetals . Oxidative cleavage of thiamine hydrochlorideand phenylpropanolamine and oxidative conversion of glutathione to glutathione disulfide, were also studied in a similar context. During the study of the oxidation of azides with NBS, it was observed that the rate of oxidation of N 3 – in an aqueous medium is proportional to [N 3 – ] and [NBS] at constant [Hg(OAc) 2 ] .…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Focusing on A and B as the major degradation products, we need to understand how our starting material breaks down at low pH. It was reported that the reaction of phenylpropanolamine with N -bromosuccinimide (as an oxidizing agent) in the presence of a HCl solution yielded benzaldehyde ammonia and acetaldehyde . A similar mechanism can be written for CpQ degradation at low pH.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the reaction of phenylpropanolamine with N-bromosuccinimide (as an oxidizing agent) in the presence of a HCl solution yielded benzaldehyde ammonia and acetaldehyde. 10 A similar mechanism can be written for CpQ degradation at low pH. The reaction occurs by a polar mechanism under acidic conditions.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
See 1 more Smart Citation